2021
DOI: 10.1155/2021/8293699
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human Umbilical Cord Blood Platelet-Rich Plasma Enhances the Beneficial Effects of Human Umbilical Cord Mesenchymal Stem Cells in Chemotherapy-Induced POF Rats

Abstract: Saving the ovarian function of premature ovarian failure (POF) patients undergoing chemotherapy is an important problem in the field of reproductive medicine. At present, human umbilical cord mesenchymal stem cells (HucMSCs) have been used in the treatment of POF, but the effect is still not optimal. The purpose of this study was to determine whether human umbilical cord blood platelet-rich plasma (ucPRP) enhances the beneficial effects of HucMSCs in the treatment of POF. First, we observed the effects of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Wang J et al found that human cord blood plateletrich plasma could promote proliferation and reduce apoptosis of hUMSCs. Co-transplantation hUMSCs with human cord blood platelet-rich plasma could increase the number of MSCs homing to the ovary of POF rats, which more effectively restored the estrous cycle and repaired damaged follicles of POF rats (176). In addition, Xu H et al indicated that co-transplantation of BMSCs and endothelial progenitor cells could promote angiogenesis in the site of osteonecrosis of the femoral head (183).…”
Section: Pretreatment and Co-transplantationmentioning
confidence: 99%
“…Wang J et al found that human cord blood plateletrich plasma could promote proliferation and reduce apoptosis of hUMSCs. Co-transplantation hUMSCs with human cord blood platelet-rich plasma could increase the number of MSCs homing to the ovary of POF rats, which more effectively restored the estrous cycle and repaired damaged follicles of POF rats (176). In addition, Xu H et al indicated that co-transplantation of BMSCs and endothelial progenitor cells could promote angiogenesis in the site of osteonecrosis of the femoral head (183).…”
Section: Pretreatment and Co-transplantationmentioning
confidence: 99%
“…Compared to that in the NR group, vimentin expression significantly increased in the HucMSCs group (231.2 ± 13.92 vs 197.0 ± 14.41, P = 0.014) and MT-HucMSCs group (243.3 ± 19.6 vs 197.0 ± 14.41, P < 0.001). PCNA is an objective index used to evaluate cell proliferative state [37]. We observed that PCNA was mainly distributed in the nuclei of endometrial epithelial cells and luminal epithelial cells (Figure 8A and B).…”
Section: Resultsmentioning
confidence: 94%
“…After obtaining informed consent, we collected donated human umbilical cord tissue from six healthy women aged 25-30 years who gave birth. According to the previous scheme [37], we prepared HucMSCs using the method of the tissue block adherence, and the specific scheme was as follows: we washed the collected umbilical cord three times with phosphate-buffered saline (PBS) (Gibco, USA, 10010) containing 10% antibiotics to remove blood and mucus, cut the umbilical cord into small pieces of tissue (1 × 1 mm 3 ) using ophthalmic scissors, and attached it to the bottom of a Petri dish. To cover the Petri dishes with tissue, we slowly added Dulbecco's modified Eagle medium (DMEM) (Gibco, USA, 31053-028) containing 10% fetal bovine serum (FBS) (Gibco, USA, 10270).…”
Section: Isolation and Culture Of Hucmscsmentioning
confidence: 99%
“…In terms of ovarian regeneration, Buigues et al [61] compared the effect of hUC plasma (rich in many GFs) to that of mobilizing G-CSF treatment and demonstrated that both therapies increased the populations of growing follicles, proliferation, and angiogenesis, in addition to restoring fertility of mice with gonadotoxic damage. Furthermore, Wang et al [210] observed the ample benefits of hUC-PRP treatment in a murine model of POI, including preserved ovarian morphology, regulated hormonal levels and estrous cyclicity, increased angiogenesis, and reduced apoptosis, with respect to the untreated groups. The up and down arrows, respectively, indicate an increase and decrease.…”
Section: Plasma and Platelet-rich Plasmamentioning
confidence: 99%